2003
DOI: 10.3109/01674820309039673
|View full text |Cite
|
Sign up to set email alerts
|

Psychological profiles among women with vulvar vestibulitis syndrome: a chart review

Abstract: The purpose of this study was to assess the prevalence and type of psychological distress in women with vulvar vestibulitis syndrome (VVS). A retrospective chart review was conducted of all women receiving a diagnosis of VVS referred to a tertiary care facility during a two-year period. Brief psychological questionnaires, including the Personality Assessment Screener, Fear of Negative Evaluation Scale, Golombok-Rust Inventory of Sexual Satisfaction, and the Phobia Rating Scale were administered. Fifty-consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
(4 reference statements)
4
40
1
6
Order By: Relevance
“…Although cases in our survey had a significantly increased odds of reporting several co-morbid chronic medical conditions, depression was the only disorder that remained strongly associated with vulvar pain in both univariate and multiple regression analysis, a finding consistent with previously reported data; [22][23][24][25][26][27][28] however, the direction of association is uncertain, and longitudinal studies are needed to better understand this relationship. Associations found between menstrual complaints and chronic vulvar pain also warrant further consideration.…”
Section: Discussionsupporting
confidence: 88%
“…Although cases in our survey had a significantly increased odds of reporting several co-morbid chronic medical conditions, depression was the only disorder that remained strongly associated with vulvar pain in both univariate and multiple regression analysis, a finding consistent with previously reported data; [22][23][24][25][26][27][28] however, the direction of association is uncertain, and longitudinal studies are needed to better understand this relationship. Associations found between menstrual complaints and chronic vulvar pain also warrant further consideration.…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, as with other dysfunctions, given the lack of clear evidence of psychological aetiology in all patients, the need for adequate physical and psychological multidisciplinary assessment, including asking about specific pain location and circumstances, is vital. Where marked or clinically significant psychological distress is established, this will inform the clinician of treatment needs and likely response to interventions 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We present some examples of dualistic conceptualization of vulval pain disorders.. Dermatologists often consider there to be two distinct subgroups, an older nulliparous group comprised of women aged between 40 and 65 and constituting the Essential Vulvodynia subgroup primarily, and a younger parous group affecting women aged between 18 and 40 years who suffer from vulvovestibulitis 8 (VVS). However our own survey revealed that a moderate level of women under 40 were diagnosed with essential vulvodynia and a higher number of the women over 40 years were diagnosed with vulvovestibulitis 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a high prevalence of depression and anxiety among vulvodynia patients Masheb et al 2005), likewise physiological research has shown unique characteristics which include, increased density of superficial nerve endings, increased immunoreactivity and nociceptor sensitivity (Bohm-Stark et al 1998, 2001Bohm-Stark et al 1999;Foster et al 2004). Such physiological peculiarities, when considered in conjunction with commonly reported psychological traits of elevated anxiety and depression (Brotto et al 2003;Granot et al 2002;Masheb et al 2005), may potentially constitute a partial predisposition to chronic vulvar pain and possibly moderate the severity of symptoms. It would, therefore, seem appropriate to study this pain syndrome from a psychophysiological perspective (Hubbard 1996;Keefe et al 2004;Severeijns et al 2005;Sullivan et al 2005;Sullivan et al 2001;Turner and Aaron 2001).…”
Section: Introductionmentioning
confidence: 97%